Development of an Antibiotic Resistance Breaker to Resensitize Drug-Resistant Staphylococcus aureus: In Silico and In Vitro Approach - Thamilselvan, Gopalakrishnan; Sarveswari, Hema Bhagavathi; Vasudevan, Sahana; Stanley, Alex; Shanmugam, Karthi; Vairaprakash, Pothiappan; Solomon, Adline Princy (Frontiers in Cellular and Infection Microbiology, 2021)
Efflux pumps are one of the predominant microbial resistant mechanisms leading to the development of multidrug resistance. In Staphylococcus aureus, overexpression of NorA protein enables the efflux of antibiotics belonging to the class of fluoroquinolones and, thus, makes S. aureus resistant. Hence, NorA efflux pumps are being extensively exploited as the potential drug target to evade bacterial resistance and resensitize bacteria to the existing antibiotics. Although several molecules are reported to inhibit NorA efflux pump effectively, boronic acid derivatives were shown to have promising NorA efflux pump inhibition. In this regard, the current study exploits 6-(3-phenylpropoxy)pyridine-3-boronic acid to further improve the activity and reduce cytotoxicity using the bioisostere approach, a classical medicinal chemistry concept. Using the SWISS-Bioisostere online tool, from the parent compound, 42 compounds were obtained upon the replacement of the boronic acid. The 42 compounds were docked with modeled NorA protein, and key molecular interactions of the prominent compounds were assessed. The top hit compounds were further analyzed for their drug-like properties using ADMET studies. The identified potent lead, 5-nitro-2-(3-phenylpropoxy)pyridine (5-NPPP), was synthesized, and in vitro efficacy studies have been proven to show enhanced efflux inhibition, thus acting as a potent antibiotic breaker to resensitize S. aureus without elucidating any cytotoxic effect to the host Hep-G2 cell lines.